Innovating The Curriculum: Analysing The Transformation Of First Year Students’ Agency In The “Cultivating Knowledge And Care” Course - Rubat du Mérac, Emiliane; Favella, Astrid (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
This paper addresses the research problem of merging curricular innovation and civic engagement, through the case study of the “Cultivating knowledge and care” course, an elective course for first year Educational Science students from Sapienza, University of Rome. Curricular innovation stems from the course embodied approach to learning. Civic engagement, instead, enters the picture as activities are conducted from the students together with their young adult counterparts from a social promotion association, supporting deaf-mute people. How do students understand their agency to have developed through the course? Reflexive thematic analysis is conducted on letters that students wrote to selected trees in the university park, imagining to write them to themselves in a mimesis exercise.